Pendidikan Karakter (Membangun Generasi Berintegritas : Pendidikan Karakter dalam Kurikulum Nasional) - Nurhalimah Pasaribu; Rizka Syamsiah Tanjung; Cut Kumala Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Character education is very important to form a strong generation, especially in facing the challenges of the digitalization and globalization era. The purpose of this article is to investigate how character education is incorporated into the national curriculum and how it functions to build students' morals and ethics. This study analyzes literature from various journals, books, and articles that discuss the theory, implementation, and policies of character education in elementary to secondary schools. The results show that character education has become an important part of the national curriculum by strengthening values ​​such as honesty, responsibility, cooperation, and anti-corruption. However, the implementation continues to face problems such as lack of teacher instruction, inconsistent implementation, and the strong influence of digital culture. Therefore, schools, families, and communities must work together so that character values ​​can be instilled properly. It is hoped that this study will help efforts to improve the quality of character education in Indonesia.